Development Of Food Doll Media For Nutrition Education Based On Food Dolls Surgery In Elementary School Children - Desi; Ismi Trihardiani (Jurnal teknologi Kesehatan Borneo, 2020)
Efforts to deal with nutrition problems include increasing nutritional knowledge in children, especially school-age children. Through their freedom of imagination, children often use puppet media as a reference that is important and fun, so that in this case the role of the media is very important in increasing children’s knowledge. This research is a pre-experiment. one group pre-post test. Data analysis in this study used the Paired Sample T-test. The subjects of this study were 35 students of public elementary school 1 Rasah Jaya, Kubu Raya Regency. Direct interview chose the data collection technique for filling out the questionnaire, to see the differences in knowledge before and after. Based on the results of the statistical test scores of knowledge before and after the intervention of 35 respondents, the p-value is 0.000 <0.05, which shows that there is a significant difference between the knowledge scores before and after the study.